TARI PADA UPACARA NGABUNGBANG DI KAMPUMG WALURAN DESA GUNUNG BATU KECAMATAN CIRACAP KABUPATEN SUKABUMI - Lasmawati, Putri Utami (2013)
The study is titled "Dance CepetIn Ceremony Ngabungbang In the village of Stone Mountain Village WaluranCiracapSukabumi District", a dance group that preserved Oleg Purwajati art. Researchers were interested in examining dance ngabungbangCepet at the ceremony, which Cepet dance is a dance that is danced in a trance or unconscious, and for the people on the dance Cepetngabungbang ceremony can be perceived as a means to achieve both a moral and spiritual needs, they believe will achieve if one wishes to dance Cepetngabungbang ceremony was held. The research problem is related to how Cepet dance background and how to structure the presentation of dance Cepetngabungbang ceremony, so the purpose of the study is that the researchers wanted to know why the trance dance and danced Cepet to describe the background and structure of the presentation of dance Cepetngabungbang ceremony. This study uses descriptive analysis and qualitative approach, collecting techniques using observational studies, interviews, documentation and libraries. The results are found in the field in KampungWaluran people still have the belief of the existence of ghosts and wild animals, so as to avoid interference and the animal spirits, held ngabungbang ritual performed by a dance that dance Cepet aimed to summon creatures smooth and the beast in order to enter into the soul of the dancer, so that the creature could be moved to other places or regions. Presentation on the dance Cepet structure has certain rules that have become a necessity as a whole that can not be changed-fox, such as mobile in the determination of dancers, time and place of execution, as well as supporting elements involved in the presentation. The conclusion of this study is Cepet Dance Ceremony Ngabungbang have an important role for the community as its medium trust people to drive bad things will happen, which is caused by the disruption beasts and spirits. Keywords: Dance Cepet, Ngabungbang ceremony, KampungWaluran, Purwajati Arts Group, Sukabumi